2020
DOI: 10.1093/rcfs/cfaa014
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 Shock and Equity Shortfall: Firm-Level Evidence from Italy

Abstract: We employ a representative sample of 80,972 Italian firms to forecast the drop in profits and the equity shortfall triggered by the COVID-19 lockdown. A 3-month lockdown generates an aggregate yearly drop in profits of about 10% of GDP, and 17% of sample firms, which employ 8.8% of the sample’s employees, become financially distressed. Distress is more frequent for small and medium-sized enterprises, for firms with high pre-COVID-19 leverage, and for firms belonging to the Manufacturing and Wholesale Trading s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
66
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(70 citation statements)
references
References 10 publications
3
66
0
1
Order By: Relevance
“…Studies that use data on small firms for European countries (e.g. Demmou, Franco, Sara and Dlugosch (2020); Carletti, Oliviero, Pagano, Pelizzon and Subrahmanyam (2020); Schivardi and Romano (2020); Cros, Epaulard and Martin (2021); Coeuré (2021)) do not rely on a structural model of the firm and often consider a simple empirical rule to project cash flow under COVID-19. Some studies also explore the question of solvency related bankruptcies, while we limit our focus to liquidity related bankruptcies, as in our previous work that also focused on SME failures in the absence of I-O network (Gourinchas et al (2020(Gourinchas et al ( , 2021a.)…”
Section: Literaturementioning
confidence: 99%
“…Studies that use data on small firms for European countries (e.g. Demmou, Franco, Sara and Dlugosch (2020); Carletti, Oliviero, Pagano, Pelizzon and Subrahmanyam (2020); Schivardi and Romano (2020); Cros, Epaulard and Martin (2021); Coeuré (2021)) do not rely on a structural model of the firm and often consider a simple empirical rule to project cash flow under COVID-19. Some studies also explore the question of solvency related bankruptcies, while we limit our focus to liquidity related bankruptcies, as in our previous work that also focused on SME failures in the absence of I-O network (Gourinchas et al (2020(Gourinchas et al ( , 2021a.)…”
Section: Literaturementioning
confidence: 99%
“…13 Philippon (2020) compares the social value of a firm to the recovery value of assets as the criteria for continuation of a firm, and designs incentive compatible government participation and guarantees. Carletti et al (2020) perform a sensitivity analysis to assess the impact on Italian firms' equity of a 3 months lockdown; they note that a recapitalization of firms facing equity shortfall as a result of the pandemic may not suffice to restore viability because many firms had weak pre-pandemic balance sheets.…”
Section: Literaturementioning
confidence: 99%
“…In addition, Acharya and Steffen recommend this as insolvency prevention [33]. Carletti et al have indicated radical decline of profits, which would continue in post-pandemic times due to the phenomenon of increasing social poverty [34]. The slight continuing decline of stock prices stated by Ramelli and Wagner is an only logic consequence of this fact [35].…”
Section: Literature Reviewmentioning
confidence: 99%